Do broadcasting ao streaming: variações audiovisuais do concerto sinfônico - Oliveira, Leandro Vasconcellos de (2019)
The aim of this thesis is to investigate the live telecasting of symphonic concerts in its history, grammar and aesthetics. The methodology is organized in three distinct and consequent axes: bibliographical survey and historical study of the broadcastings from its origins to the present day; a case study of one of these performances, in its qualitative and quantitative aspects; an alternative proposal for the audiovisual solutions to an event of this kind, based on the technical parameters in the former case study analysis. As a result, the thesis updates the theoretical apparatus of reference on the subject; inaugurates the studies of the field in Portuguese language; critically analyzes the methodology of Berlin Philharmonic's Digital Concert Hall app, evaluating its aesthetic effectiveness, as well as the experimental and technical feasibility of some alternatives to it